2003
DOI: 10.1653/0015-4040(2003)086[0178:eoiooi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insecticides on Orius Insidiosus (Hemiptera: Anthocoridae), Measured by Field, Greenhouse and Petri Dish Bioassays

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
2
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 15 publications
3
41
2
12
Order By: Relevance
“…Even though the type of substrate used in the testing procedures might affect the results, particularly if using plant substrates, due to the differences in leaf hairiness, cuticular waxes, leaf veins, etc. (reviewed in Croft, 1990), the toxicity of emamectin to this predatory insect was similar in the laboratory using an inert substrate and in semi-field and field conditions using cotton plants (Studebaker and Kring, 2003).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Even though the type of substrate used in the testing procedures might affect the results, particularly if using plant substrates, due to the differences in leaf hairiness, cuticular waxes, leaf veins, etc. (reviewed in Croft, 1990), the toxicity of emamectin to this predatory insect was similar in the laboratory using an inert substrate and in semi-field and field conditions using cotton plants (Studebaker and Kring, 2003).…”
mentioning
confidence: 90%
“…Similarly, no deleterious effects have been reported in other predatory species, such as the larvae of Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae) or the mites Euseius citrifolius (Denmark and Muma) (Acari: Phytoseiidae) and Euseius alatus (DeLeon) (Acari: Phytoseiidae) (Reis et al, 2004;Ferreira et al, 2006). In contrast with these results, Studebaker and Kring (2003) reported that the predatory bug Orius insidiosus (Say) (Heteroptera: Anthocoridae) was very sensitive to fresh residues of emamectin in semi-field conditions using cotton plants. Even though the type of substrate used in the testing procedures might affect the results, particularly if using plant substrates, due to the differences in leaf hairiness, cuticular waxes, leaf veins, etc.…”
mentioning
confidence: 91%
“…The effect of traditional and reduced-risk insecticides to non-target organisms is well documented. To mention a few examples, studies on natural enemies of thrips include Geocoris punctipes [14] [19], and Amblyseius spp. [20].…”
Section: Prior To 2008 Most Of the Chemical Control For Flower Thripsmentioning
confidence: 99%
“…However, the activity of indoxacarb against the sucking insects is weaker than for Lepidoptera because of its slower bioactivation, lower sensitivity and a less favorable method of oral uptake in the sucking insects. Indoxacarb allows most predators and immature wasp parasites to survive (Hewa-Kapuge et al 2003;Studebaker and Kring 2003). However, the wet residues of indoxacarb are toxic to bees and adult wasp parasites.…”
Section: Insecticides For Lepidopteramentioning
confidence: 99%
“…Emamectin benzoate toxicity is broader spectrum than methoxyfenozide, tebufenozide or indoxacarb, which is a benefit in that it kills a wide variety of lepidopterans (Argentine et al 2002). However, its broad-spectrum activity also makes fresh residues toxic to natural enemies (Studebaker and Kring 2003). Natural enemy survival improves after about 5 days due to rapid photodegradation.…”
Section: Insecticides For Lepidopteramentioning
confidence: 99%